A "Power and Influence" political archetype: the dynamics of public support. (3rd March 2019) - Cavana, Robert Y.; Forgie, Vicky E.; van den Belt, Marjan; Cody, John R.; Romera, Alvaro J.; Wang, Keming; Browne, Chris A.
Abstract: Systems archetypes are effective in communicating complex behaviour with relatively simple structures, across a wide range of topics. The "power dynamics" between different power holders are critically important in decision making when it comes to formulating and implementing policies. This topic was explored at a four‐day Australasian systems workshop run in New Zealand. A synthesis approach was combined with analytical procedures from system dynamics (SD). Building on Rahn's "Fear and Greed" political archetype, a conceptual "Power and Influence" political archetype was developed. This political archetype shows the impact of public support. It is used to analyse a crowdfunding story in New Zealand. A small SD concept model was subsequently constructed to test this story and evaluate alternative public support scenarios. A library of political archetypes and concept models would be an asset for the field of SD and provide a means of synthesising insights from case studies and social theory. © 2019 System Dynamics Society